A retrospective study of probiotics for the treatment of children with antibiotic-associated diarrhea. Issue 23 (5th June 2020) - Rui, Xue; Ma, Shu-xia
Abstract : Abstract: This retrospective study aimed to explore the benefits and safety of probiotics (live combined Bacillus subtilis and Enterococcus faecium granules with multivitamines) for the treatment of children with antibiotic-associated diarrhea (AAD). A total of 72 children with AAD were analyzed in this study. Of these, 36 children received routine treatment plus probiotics, and were assigned to a treatment group. The other 36 children underwent routine treatment alone, and were assigned to a control group. Patients in both groups were treated for a total of 7 days. The efficacy and safety were evaluated by duration of diarrhea (days), number of dressings needed daily, abdominal pain intensity, stool consistency (as assessed by Bristol Stool Scale (BSS)), and any adverse events. After treatment, probiotics showed encouraging benefits in decreasing duration of diarrhea (days) ( P  < .01), number of dressings needed every day ( P  < .01), abdominal pain intensity ( P  < .01), and stool consistency (BSS (3–5), P  < .01; BSS (6–7), P  < .01). In addition, no adverse events were documented in this study. The findings of this study demonstrated that probiotics may provide promising benefit for children with AAD. Further studies are still needed to warrant theses findings.